The use of personal pronouns and the observance of Grice’s principles in political interviews / Nik Nur Laila Nik Mustapha - Nik Nur Laila, Nik Mustapha (2017)
The current study examined the discourse of the current Prime Minister of Malaysia, Dato’ Seri Najib Razak (DSNR) and the current Leader of Opposition Malaysia; Parti Keadilan Rakyat, Dato’ Seri Anwar Ibrahim (DSAI), with a view to investigate their strategic use of personal pronouns I and We and their adherence to Grice’s Cooperative Principles (1975) in political interviews. The analysis of this study will help shed some light on how the two politicians employ the strategies of using personal pronouns to generate implicature which can affect the overall outcome of the interviews, especially the audience’s understanding and acceptance of the message. Additionally, the study will also help to give a complete picture of what the two politicians are conveying in the political interviews and explain the ways these politicians conform to Grice’s Cooperative Principles when they were asked questions on any politically related issues.